The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15288/jsad.2016.77.649
|View full text |Cite
|
Sign up to set email alerts
|

Restless Sleep and Variable Sleep Timing During Late Childhood Accelerate the Onset of Alcohol and Other Drug Involvement

Abstract: ABSTRACT. Objective: Limited prospective data indicate that premorbid sleep disturbances elevate the risk for subsequent alcohol and other drug problems, yet the implications for subsequent substance involvement trajectories remain unclear. In the present analyses, we examined risk associations between sleep characteristics during late childhood and the onset of substance use and substance use disorders into adulthood. Method: A sample of 707 children was recruited at ages 9-13 years and followed over seven ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Growing evidence links sleep to alcohol use and alcohol‐related problems (e.g., Brower et al., ; Hasler et al., , ; Roehrs and Roth, , ; Wong et al., ). Along with sleep disturbances, many studies have reported that evening chronotypes (i.e., having a preference for later timing of sleep and activity) engage in greater alcohol use.…”
Section: Sleep Timing Eveningness and Alcohol Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence links sleep to alcohol use and alcohol‐related problems (e.g., Brower et al., ; Hasler et al., , ; Roehrs and Roth, , ; Wong et al., ). Along with sleep disturbances, many studies have reported that evening chronotypes (i.e., having a preference for later timing of sleep and activity) engage in greater alcohol use.…”
Section: Sleep Timing Eveningness and Alcohol Responsementioning
confidence: 99%
“…Notably, eveningness is often accompanied by more variable sleep timing (Soehner et al., ; Wittmann et al., ), which is also associated with alcohol involvement and thus is a hypothesized factor linking eveningness and alcohol problems (Wittmann et al., ). Cross‐sectional studies link larger weekday–weekend differences in sleep timing with greater alcohol, tobacco, and marijuana use (O'Brien and Mindell, ; Pasch et al., ), while longitudinal studies report that larger weekday–weekend differences in sleep duration predict more alcohol use disorder (AUD) symptoms 3 and 5 years later (Hasler et al., ), and greater self‐reported variability in sleep timing predicts an earlier age of onset for AUD (Hasler et al., ). Examining multiple components of sleep (e.g., self‐reported preference of sleep timing, actual sleep timing, and variability in actual sleep timing) within the same study is important to further understand which domains of sleep are most related to risk for heavy alcohol involvement.…”
Section: Sleep Timing Eveningness and Alcohol Responsementioning
confidence: 99%
“…Reversed causation -from insomnia to substance use-may also play a role. For example, adolescents with low sleep quality have shown a stronger inclination for later substance use (Hasler et al, 2016), although strong causal inferences cannot be made based on longitudinal designs.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists for the reverse relationship as well, with premorbid insomnia 21 and generalized sleep problems [39][40][41] predicting later cannabis use. This effect appears strong in early development, such that early childhood sleep deficits predict cannabis use in later adolescence 22,42-44 and sleep factors during adolescence predict adult cannabis use 21, 45 . Lastly, endorsements of an adolescent eveningness chronotype is associated with follow-up reports of increased cannabis use controlling for baseline adolescent substance use 40 .…”
Section: Introductionmentioning
confidence: 99%